COMPARATIVE RESEARCHE REGARDING METABOLIC PROFILE OF THE CALIFORNIAN, NEW ZEALAND WHITE, GRAND CHINCHILLA MEAT RABIT BREEDS AND THE F1 NZCH HYBRIDS - DANIELA-MARCELA TOBĂ (GOINA); MARIOARA NICULA; D. MORAR; M. BURA; D. DRONCA; SIMINA ILIANA SILION (NEO) (Scientific Papers Animal Science and Biotechnologies, 2023)
Precious biological characteristics of rabbits make their breeding a very profitable occupation. The rabbit meat, organoleptically same to the white meat, is rich in proteins, but low in fats. Biological researched done in direction to elucidate the biochemical systems that are the basis for organism physiological processes, have revealed that the level in which this process are develop directly influence the rabbits productivity capacity. 60 rabbit’s heads was used as biological material, distributed in: 15 Californian, 15 New Zeeland White, 15 Grand Chinchilla and 15 F1NZCH hybrids obtained from cross-breeding the New Zeeland White as maternal form and Grand Chinchilla as paternal form. Blood was sampled from the rabbit and was biochemical analyzed. The studied indices were: total protein, albumin, urea, uric acid, creatinine, total bilirubine, cholesterol, triglyceride and glucose. The experimental lot formed from F1 NZCH hybrids registered a concentration of 2.1 mg/dl uric acid, and in the other three lots the concentration was under 2 mg/dl. In all four lots, uric acid value was in normal limits. The determined creatinine registered very low values, under 1 mg/dl, at the low limit of reference values. At hybrids from New Zeeland White as maternal form and Grand Chinchilla as paternal form, in equal environmental conditions, the serum biochemical analysis haven’t registered significant differences compared to pure breeds individuals.